2019
DOI: 10.1071/an17809
|View full text |Cite
|
Sign up to set email alerts
|

Improved region-specific emission factors for enteric methane emissions from cattle in smallholder mixed crop: livestock systems of Nandi County, Kenya

Abstract: Abstract. National greenhouse-gas (GHG) inventories in most developing countries, and in countries in Sub-Saharan Africa in particular, use default (Tier I) GHG emission factors (EFs) provided by the Intergovernmental Panel on Climate Change (IPCC) to estimate enteric methane (CH 4 ) emissions from livestock. Because these EFs are based on data primarily from developed countries, there is a high degree of uncertainty associated with CH 4 emission estimates from African livestock systems. Accurate Tier II GHG e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 25 publications
(28 reference statements)
2
45
4
Order By: Relevance
“…The latter is still far away though, but the idea is that mitigation successes can from now on not only be identified but also reliably be quantified. Recent work tries to improve on the generic IPCC emission factors as most were developed on estimates derived for systems in developed countries, which are likely not transferable to low and middle income countries given significant differences in management intensity, climates, soils, or even often animal breeds (e.g., Pelster et al, 2017;Goopy et al, 2018;Ndung'u et al, 2018;Richards et al, 2018;Zhu et al, 2018Zhu et al, , 2020. Currently, individual agricultural practices and technologies need to be similarly assessed in terms of meeting simultaneously the demands of pillars 1 and 2.…”
Section: Pillar 3: Mitigationmentioning
confidence: 99%
See 3 more Smart Citations
“…The latter is still far away though, but the idea is that mitigation successes can from now on not only be identified but also reliably be quantified. Recent work tries to improve on the generic IPCC emission factors as most were developed on estimates derived for systems in developed countries, which are likely not transferable to low and middle income countries given significant differences in management intensity, climates, soils, or even often animal breeds (e.g., Pelster et al, 2017;Goopy et al, 2018;Ndung'u et al, 2018;Richards et al, 2018;Zhu et al, 2018Zhu et al, , 2020. Currently, individual agricultural practices and technologies need to be similarly assessed in terms of meeting simultaneously the demands of pillars 1 and 2.…”
Section: Pillar 3: Mitigationmentioning
confidence: 99%
“…A key aspect of many of the tools is the adherence to the FAO GHG emission factors with limited ability to update these numbers or to include other GHG emission model formulations. While this is logical from a modeling perspective, such consistency in analyses does mean that most assessment frameworks use emission factors that are based on estimates derived for systems in developed countries under different climates with different breeds and overall completely different production systems (e.g., Goopy et al, 2018;Ndung'u et al, 2018;Richards et al, 2018). As a consequence, this can lead to substantial over/under-estimation of GHG emissions and of GHG emission intensities (see example 2017A standardized household survey approach aiming to quantify the three pillars of CSA for a given system.…”
Section: The Current State Of Climate Smart Agricultural Assessment Fmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a significant limitation to the utility of these equations is that measurements have been conducted only on animals fed for production (i.e. at maintenance and above), whereas it has been recently demonstrated that cattle regularly experience episodes of significant seasonal weight loss in African smallholder systems (10,11) .…”
mentioning
confidence: 99%